2020
DOI: 10.1109/access.2020.2980889
|View full text |Cite
|
Sign up to set email alerts
|

Improved Adaptive Robust Control for Low Voltage Ride-Through of Front-End Speed Regulation Wind Turbine

Abstract: This paper proposes a low voltage ride-through (LVRT) control method for the front-end speed regulation (FESR) wind turbine based on an improved adaptive robust control (IARC) to find the solution of the generator parameter variation by grid voltage dip and enhance the LVRT capability of the FESR. First, the FESR system mathematical models and the control objective of LVRT are analyzed. Then, in the improved adaptive robust controller, the Lyapunov function for three subsystems and the energy function of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To investigate control strategies, various studies have shown that a third-order mathematical model of SG is sufficient to satisfy engineering demands considering the complexity of control law modeling. In this case, the model of an electrically excited SG is given by [26], [27]:…”
Section: B Mathematical Model Of Sgmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate control strategies, various studies have shown that a third-order mathematical model of SG is sufficient to satisfy engineering demands considering the complexity of control law modeling. In this case, the model of an electrically excited SG is given by [26], [27]:…”
Section: B Mathematical Model Of Sgmentioning
confidence: 99%
“…SG excitation control allows to flexibly adjust the output voltage and power, thus improving the transient and steadystate grid-connected operation performance of SRDM-based hybrid drive WTs. Recently, [25] and [26] synthesized an adaptive robust excitation controller for ensuring the voltage stability and reactive power carrying capacity of hybrid drive WTs. The nonlinear effects caused by the strong coupling in the transmission system were reduced by including additional error compensators, but the required accurate system parameters are difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Yin et al [19] summarised the current status as well as the future prospects of CVT‐based WTs and pointed out that the mechanical, hydraulic and hydro‐mechanical CVTs all have good potential to be effectively‐employed in high‐power WTs. Dong et al [20, 21] investigated the control methods of front‐end speed regulation WT to optimise the output power and to improve the system low‐voltage ride‐through capability. Lin et al [22] analysed the frequency regulation ability of their proposed converter‐free offshore hydrostatic WTs.…”
Section: Introductionmentioning
confidence: 99%
“…Speed regulating differential mechanism (SRDM), expected to be effective in regulating output frequency of SG and eliminating undesirable effects induced by fully-or partially-rated converters, possesses advantages for VSCF wind turbines (WTs) in terms of improving energy transmission efficiency and system operational reliability as well as reducing equipment manufacturing and maintenance costs [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Using the advanced technologies of mechanical transmission and servo control, SRDM can be adopted at the front-end of SG to get constant-frequency power regardless of the changing wind rotor speed.…”
Section: Introductionmentioning
confidence: 99%
“…e essential difference of the FSCWT is that it uses a hydraulic torque converter named WinDrive to regulate the speed of the generator at the frontend of the turbine [16], greatly improving the low voltage ride-through capability of the wind turbine and increasing the advantage of reactive power output [17]. At the same time, the EESG is directly coupled with the power grid, which can provide certain transient support for the system in case of failure or instability of the access system.…”
Section: Introductionmentioning
confidence: 99%